2003
DOI: 10.1093/nar/gkg211
|View full text |Cite
|
Sign up to set email alerts
|

Structural transition from antiparallel to parallel G-quadruplex of d(G4T4G4) induced by Ca2+

Abstract: Guanine quadruplex (G-quadruplex) structures are formed by guanine-rich oligonucleotides. Because of their in vivo and in vitro importance, numerous studies have been demonstrated that the structure and stability of the G-quadruplex are dependent on the sequence of oligonucleotide and environmental conditions such as existing cations. Previously, we quantitatively investigated the divalent cation effects on the antiparallel G-quadruplex of d(G4T4G4), and found that Ca2+ induces a structural transition from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
111
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(124 citation statements)
references
References 38 publications
12
111
0
Order By: Relevance
“…Under our conditions, transitions were observed by ESI-MS only for the strands d(G 3 G 3 ) and d(G 4 G 3 ), but not for d(G 4 G 4 ) and d(G 3 G 4 ), even when the latter were incubated in the NH 4 ϩ solution for more than 10 days. Miura et al found that the antiparallel bimolecular quadruplex formed by the strand d(G 4 G 4 ) was generated at low concentrations of Na ϩ and K ϩ , and that the bimolecular species was converted to the parallel four-stranded quadruplex when the concentrations of both alkali ions were increased in a range of 65-225 mM, the K ϩ being more 4 and finally to a G-wire, and the transitions were induced by the presence of Ca 2ϩ [32].°Sen°and°Gilbert°proposed°that°the°foldback°bimo-lecular quarduplexes were overstabilized intermediates and expected all of the quadruplexes formed by single, double, or four strands to be finally converted into four-stranded°parallel°quadruplexes° [30].°In°this°case, the transitions of the bimolecular species to the tetramolecular one are probably facilitated by specific structural and stability characteristics of the bimolecular quadruplexes. If 2 contains two dangling guanine residues residing at the same end of the quadruplex.…”
Section: Detections Of Trimolecular and Tetramolecular Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Under our conditions, transitions were observed by ESI-MS only for the strands d(G 3 G 3 ) and d(G 4 G 3 ), but not for d(G 4 G 4 ) and d(G 3 G 4 ), even when the latter were incubated in the NH 4 ϩ solution for more than 10 days. Miura et al found that the antiparallel bimolecular quadruplex formed by the strand d(G 4 G 4 ) was generated at low concentrations of Na ϩ and K ϩ , and that the bimolecular species was converted to the parallel four-stranded quadruplex when the concentrations of both alkali ions were increased in a range of 65-225 mM, the K ϩ being more 4 and finally to a G-wire, and the transitions were induced by the presence of Ca 2ϩ [32].°Sen°and°Gilbert°proposed°that°the°foldback°bimo-lecular quarduplexes were overstabilized intermediates and expected all of the quadruplexes formed by single, double, or four strands to be finally converted into four-stranded°parallel°quadruplexes° [30].°In°this°case, the transitions of the bimolecular species to the tetramolecular one are probably facilitated by specific structural and stability characteristics of the bimolecular quadruplexes. If 2 contains two dangling guanine residues residing at the same end of the quadruplex.…”
Section: Detections Of Trimolecular and Tetramolecular Speciesmentioning
confidence: 99%
“…As an intermediate, the bimolecular structure can°vary°from°one°form°to°another° [30] 2 and unfold the structure; the strands then rearrange alignment in the denatured state and pair with other strands to form more stable parallel structures° [32].°Xu°et°al.°indicate°a°possible°shift°be-tween the mixed-parallel/antiparallel and the chairtype quadruplexes formed by the human telomere sequence°in°K ϩ°i on°solution° [36].°In°the°present°work, we show that two of the four bimolecular quadruplexes are not terminal products and are converted to more stable structures. The transition rates probably depend on the stabilities and specific structures of the bimolecular quadruplexes, as well as on the solution conditions.…”
Section: Spectra Of the Bimolecular And Higher-order Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…For parallel G quadruplex structure formation, a positive band at ∼265 nm and a negative band at ∼240 nm have been observed, whereas the signatures of an antiparallel G quadruplex structure are a negative band at ∼260 nm and a positive band at ∼295 nm (Miyoshi et al 2003;Paramasivan et al 2007;Kypr et al 2009;Vorlícǩová et al 2012;Randazzo et al 2013). Both PSD-95 Q1 and Q2 exhibit the signature of a parallel G quadruplex structure, even in the absence of K + ions (Fig.…”
mentioning
confidence: 93%
“…It was found that Ca 2+ and molecular crowding induced G-wire formation of d(G 4 T 4 G 4 ). 40,41 We further demonstrated that a single G to A substitution in the loops leads to a drastically different structure under molecular crowding conditions. Under crowding conditions, d(T 2 (G 3 T 2 G) 3 G) folds into very long G-wires, whereas d((G 3 T 2 A) 3 G 3 ) folds into antiparallel G-quadruplexes.…”
Section: Dna Logic Gates Based On Structural Polymorphismsmentioning
confidence: 76%